The Effect of Baby Massage on Weight Gain in Babies Aged 4–6 Months in the Working Area of the Kepenuhan Community Health Center - Julainah; Yuyun Bewelli Fahmi (International Journal of Health Engineering and Technology, 2025)
This study investigates the effect of infant massage on weight gain among infants aged 4 to 6 months in the Kepenuhan Community Health Center area. The research aims to evaluate whether massage therapy can serve as a cost-effective, non-pharmacological intervention to promote healthy growth in resource-limited settings. A quantitative pre-experimental design with a one-group pretest-posttest approach was employed, involving 20 infants selected through saturated sampling. Data were collected using standardized digital infant scales with 0.01 kg precision, following a structured protocol for massage administered by trained healthcare personnel. Data analysis involved descriptive statistics and paired sample t-tests to determine the significance of weight change pre- and post-intervention. Results revealed a significant mean weight increase of 0.435 kg (p = 0.000). The findings support the hypothesis that infant massage positively influences weight gain in this age group. The study concludes that infant massage is an effective, accessible strategy to enhance growth and development, with implications for integrating it into routine primary healthcare practices. Future research should consider larger samples and control groups to strengthen evidence.